Kebergantungan skor ujian karangan Bahasa Cina murid Tahun Enam Sekolah Jenis Kebangsaan / Quek Weng Kim - Quek, Weng Kim (2010)
The purpose of the study is to examine the relationship of the relative effects of writing tasks and raters, and the combined impact of the numbers of tasks and raters based on different rating procedures on the dependability of writing score from the perspective of G-theory. A total of 120 Year Six pupils from 10 schools at one of the district in Perak have participated in the study. In generalizability study (G-study), random model partially nested p × (r: t) design is employed. Twelve experienced raters are randomly divided into four groups to conduct the marking on two different sessions. Analysis of variance components shows that the effects of tasks and raters are dependent on the different rating procedures. In decision study (D-study), based on the same design as G-study, dependability score for different rating procedures is reported. The findings indicate that the increase of the numbers of writing tasks is more efficient than that of raters in increasing the accuracy of measurement. The results of this study also indicate that aspect of language use and mechanics (especially combined with analytic method), require the combination of less number of tasks and raters to achieve high generalizability coefficient compared to aspect of content and organization while analytic method has the edge on holistic method. Based on the mixed model, all rating procedures are managed to obtain the generalizability coefficient of more than .80 with only a single combination of vi writing task (fixed facet) and rater. It is suggested that writing assessment in primary school level especially Chinese essay test should consider in employing analytic method and emphasize on assessing of language use and mechanics. Besides, to achieve high dependability of writing score based on the current study, at least the combination of three writing tasks and three raters are recommended.